Preparation method of electrode plate

By adding easy-to-sublimate pore-making agent to the slurry of the lithium battery, forming a pore structure, the problems of rate performance and internal resistance of the lithium battery are solved, and more efficient lithium ion transmission and battery performance improvement are achieved.

CN119725393APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311267925.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing lithium battery technology is difficult to effectively improve the battery's rate performance and reduce the internal resistance during charging and discharging. Especially in thick-electrode batteries, the ion transmission path is complex and leads to slow dynamics.

Method used

By adding easy-to-sublimate pore making agent to the slurry, the pore making agent is sublimated by heating conditions, leaving a regular pore structure and increasing the pore volume of the pole sheet, thereby providing a channel for the transmission of lithium ions and reducing transmission resistance.

Benefits of technology

This process effectively improves the rate performance of lithium-ion batteries, especially in thick-electrode batteries, which significantly improves the transmission rate of lithium-ion, reduces the internal resistance of the battery, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a preparation method of an electrode pole piece, the electrode pole piece comprises a current collector and an electrode coating attached to the current collector, and the electrode is a positive pole piece or a negative pole piece; the electrode coating is coated on the current collector in a slurry coating manner, and the specific process is as follows: 1) preparing slurry: adding a pore-forming agent into the slurry containing an electrode coating material, 2) coating the slurry on the current collector, drying and rolling; and 3) carrying out secondary baking to sublimate the pore-forming agent, and removing the pore-forming agent in the coating slurry. According to the process, the transmission path of lithium ions in the battery pole piece can be improved, and the ion transmission internal resistance in the battery charging and discharging process is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium batteries and discloses a process for preparing a high-power electrode plate of a lithium battery. Background Art

[0002] Batteries have played an important role in promoting the popularity of portable electronic devices and driving the revolution of modern information technology. Rechargeable lithium-ion batteries are currently the most popular battery chemistry due to their low maintenance cost, light weight, and high energy density compared to other types of batteries. However, substantial improvements in lithium battery technology are still needed to meet the growing demand for high energy and high power properties. Recent progress in developing lithium-ion batteries with high operating voltage and high specific capacity through novel material design is expected to further improve battery energy density. Despite these advances in material chemistry, it is often found that the behavior of active ingredients differs from theoretical expectations, resulting in significant energy losses and undesirable characteristics during battery operation. The difference between actual performance and expected results mainly stems from kinetic limitations in multiple dimensions and time scales. Compared with the perspective of changing materials, structural design provides a better solution that can be applied to more material systems, reduce solid-state diffusion distances, and increase ion transport channels.

[0003] Another common strategy is to increase the battery active material loading, i.e., surface density, or reduce the proportion of auxiliary materials to achieve high energy density goals. Due to the substantial increase in the payload, numerous challenges are faced, including poor mechanical stability and, most importantly, increased polarization. Although nanostructures have been shown to improve electrochemical performance, the increase in electrode thickness and the more complex ion transport pathways along the vertical direction result in slower transport kinetics in thick electrodes with nanoscale structures. While a great deal of effort has been focused on the fine design and synthesis of nanoscale materials, little attention has been paid to the distribution of pores in various dimensions within the electrode sheet and the changes in ion transport pathways during charge and discharge.

[0004] In response to the above technical problems, the currently reported methods include preparing high-power electrode plates through laser drilling or using a template with a wire mesh as the hole to improve the ion transmission path, but the above methods are difficult to achieve large-scale production. Summary of the invention

[0005] In view of the above problems, the present invention provides a high-power electrode plate preparation process, which can improve the rate performance of lithium-ion batteries and effectively reduce the internal resistance of the battery during charging and discharging.

[0006] The present invention protects a high-power electrode plate preparation process, the electrode can be a positive electrode plate or a negative electrode plate, the electrode plate includes an electrode coating and a metal foil current collector, the electrode coating is coated on the metal foil by slurry coating, the slurry includes a positive electrode or a negative electrode active material, a solvent, a binder, a conductive agent, etc., and a pore-forming agent needs to be added to the slurry, the pore-forming agent is an organic or inorganic substance that is easy to sublimate under heating conditions, the pore-forming agent can be a single component, or a combination of multiple pore-forming agents, preferably the pore-forming agent accounts for 0.5%-15% of the total weight of the battery slurry solid, the solid content of the slurry is generally 30%-80%, and the high-power electrode preparation process includes slurry The process includes material stirring, coating, rolling and baking. The drying temperature in the coating process should be lower than the sublimation temperature of the pore-forming agent minus 30°C. The rolling pressure is usually 10 tons to 200 tons. The baking is a process of heating the pole piece after the rolling process. The purpose of heating is to remove the pore-forming agent in the pole piece. The heating conditions are determined according to the sublimation temperature of the added pore-forming agent. The temperature is greater than the sublimation temperature of the pore-forming agent plus 20°C. After the pore-forming agent sublimates, a regular pore structure will be left, which increases the porosity of the pole piece after rolling. The porosity is usually in the range of 15% to 50%. The pore structure can provide a channel for the transmission of lithium ions during the charge and discharge process of the battery, reduce the resistance to lithium ion transmission, and increase the rate performance of the battery.

[0007] Beneficial effects:

[0008] The present invention adds a pore-forming agent during the slurry stirring process, and the pore-forming agent is coated on the metal foil together with the slurry through a coating process. The coated electrode is rolled through a rolling process. The electrode still contains the pore-forming agent after rolling. At this time, the electrode is baked. The pore-forming agent sublimates at a certain temperature and leaves a pore structure. First, the pore structure provides a channel for ion transmission, increases the transmission rate of lithium ions in the electrode, and is beneficial to the improvement of battery power performance, especially has a great effect on the rate performance of thick electrode batteries. Second, because the pore-forming agent is added after the rolling process, the pore structure is not only the pore structure of the electrode, but also the pore structure of the electrode is not the same as the pore structure of the electrode. Sublimation occurs during the rolling process, so the rolling process does not affect the pore structure in the electrode piece. The method of the present invention is different from the metal mesh template pore making technology. The metal mesh template pore making is during the electrode coating and film forming process, and the metal mesh is taken out before rolling. Therefore, the subsequent rolling process of the electrode will inevitably affect the original pore structure or the battery electrode piece cannot be rolled. Third, the pore structure and size of the electrode piece can be dynamically controlled. The pore structure and size can be adjusted by adjusting the type of pore-forming agent and the addition ratio to achieve customized preparation of battery electrodes with different requirements. Fourth, the process is easy to implement and is convenient for large-scale production. DETAILED DESCRIPTION

[0009] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0010] The present invention protects a process for preparing a high-power electrode pole piece. The electrode can be a positive pole piece or a negative pole piece. The pole piece includes two parts: an electrode coating and a current collector. The positive electrode of the current collector is aluminum foil, and the negative electrode is copper foil. The electrode coating is coated on the metal foil by slurry coating. The slurry includes positive or negative electrode active materials, solvents, binders, conductive agents, etc. The positive electrode active materials are lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, lithium iron manganese phosphate and other lithium battery positive electrode materials, and the negative electrode active materials are graphite, silicon carbon and other negative electrode materials. The solvent is water or N-methylpyrrolidone. The binder positive electrode is polyvinylidene fluoride (PVDF), the negative electrode is sodium carboxymethyl cellulose and styrene-butadiene rubber, and the conductive agent is one or both of conductive carbon black (SP) or carbon nanotubes.

[0011] In addition, a pore-forming agent needs to be added to the slurry. The pore-forming agent is an organic or inorganic substance that is easy to sublimate under heating conditions. The pore-forming agent can be a single component or a combination of multiple pore-forming agents. The high-power electrode preparation process includes several steps of slurry stirring, coating, rolling, and baking. The baking is a step of heating the pole piece after the rolling process. The purpose of heating is to remove the pore-forming agent in the pole piece. The heating conditions are determined according to the sublimation temperature of the added pore-forming agent. The temperature needs to be greater than the sublimation temperature of the pore-forming agent plus more than 20°C. This process can improve the porosity of the pole piece after rolling, effectively reduce the internal resistance of ion transmission during battery charging and discharging, and increase the rate performance of lithium-ion batteries. The following is a specific embodiment.

[0012] Example 1

[0013] This embodiment adopts the above process path to prepare high-power electrode plates. The positive electrode uses lithium cobalt oxide (LCO) material as the active material. The positive electrode formula is 95% LCO + 2% PVDF + 3% SP. The positive electrode is divided into group A and group B. No pore-forming agent is added to group A, and pore-forming agent ferrocene is added to group B. The amount of ferrocene added is 5% of the total weight of the slurry solid content. The solid content of the positive electrode group A and group B is 67%. The negative electrode formula is 95% graphite + 2% SBR + 2% CMC + 1% SP, the negative electrode is also divided into group C and group D, no pore-forming agent is added to group C, and pore-forming agent ferrocene is added to group D, and the amount of ferrocene added is 5% of the total weight of the solid content of the slurry. The solid content of the negative electrode group C and group D is 55%. The positive electrode of the current collector is aluminum foil, and the negative electrode is copper foil. The positive and negative electrode slurries are prepared into pole pieces through coating and rolling processes, wherein the baking temperature for removing the solvent in the positive electrode coating process is 70°C, and the baking temperature for removing the solvent in the negative electrode coating process is 60°C. The coating surface density of the positive electrode of group A after removing the solvent is 19.3 mg / cm 2 After removing the solvent, the coating surface density of group B positive electrode is 20.26 mg / cm 2 The negative electrode coating density of group C is 9.3 mg / cm 2 After removing the solvent, the coating surface density of the negative electrode of group D is 9.76 mg / cm 2 The thickness of the positive electrode after rolling is 120μm±2μm, and the rolling pressure is 50 tons. The thickness of the negative electrode after rolling is 160μm±2μm, and the rolling pressure is 55 tons. Group A and Group C do not contain pore-forming agent, and no heating pore-making process is required. The pole pieces of Group B and Group D still contain the pore-forming agent ferrocene. The pole pieces of Group B and Group D are heated to remove the pore-forming agent in the pole pieces. The heating temperature is 180℃, and the heating time is 1 hour. After the pore-forming agent ferrocene in the heated pole pieces is sublimated, a pore structure will be left in the pole pieces. The pore can provide a channel for lithium ion transmission, increase the battery's rate performance, that is, the battery's power characteristics, and improve the battery's rate performance. The diaphragm is made of PE material, the electrolyte is a mixed solvent of 1mol / L lithium hexafluorophosphate + ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC) (the solvent volume ratio is 3:4:3), and the whole battery is assembled for testing. The size of the positive electrode plate is 74mm*106mm, and the size of the negative electrode plate is 76mm*108mm. The assembled battery adopts the stacking process, and the number of stacks is 5 positive electrodes and 6 negative electrodes. The stacked battery is baked at 85℃ for 24 hours to remove moisture in the battery. After the baked battery is injected with liquid and formed, a battery with a capacity of about 2Ah is prepared. The battery is assembled using different groups of pole pieces, and the battery rate performance and the porosity of the pole pieces after rolling of different groups are tested. The battery numbers and test results of different combinations are as follows:

[0014]

[0015]

[0016] In the embodiment, the 10C discharge capacity retention rate of group a (10C discharge capacity value / 1C discharge capacity value*100%) is 80.1%-80.5%, the 10C discharge capacity retention rate of group b is 93.2%-93.5%, and the 10C discharge capacity retention rate of group c is 91.1%-91.7%, which are 13% and 11% higher than those of group a, respectively. At the same time, the battery internal resistance value at 50% SOC (50% power) is tested by an AC internal resistance tester. The internal resistance is d<b<c<a in the order of small to large charge. The results of the rate test and internal resistance test are mainly due to the use of a pore-forming agent in the positive electrode of group b. Electrode A and group C used electrode B containing a pore-forming agent. The porosity of the battery electrode containing a pore-forming agent was increased compared with that of the electrode without a pore-forming agent, which reduced the resistance to ion transfer in the electrode, increased the lithium ion transfer efficiency, and effectively improved the rate performance of the battery. The 10C discharge capacity retention rate of group D was 99.1%-99.3%, which was better than that of groups A, B, and C. This was mainly due to the addition of pore-forming agents to the positive and negative electrodes in group D during the preparation process, which increased the porosity of the positive and negative electrode sheets. The presence of a pore structure inside the electrode effectively reduced the resistance to ion transfer during battery discharge, so the rate performance of group D batteries was the best.

[0017] Example 2

[0018] In this embodiment, the high-power electrode plate is prepared by the above process path. The positive electrode uses lithium cobalt oxide (LCO) material as the active material. The positive electrode formula is 95% LCO+2% PVDF+3% SP. The positive electrodes are divided into group A, group B, group C and group D. No pore-forming agent is added to group A, pore-forming agent ferrocene is added to group B, and the amount of ferrocene added is 5% of the total weight of the slurry solid content. The pore-forming agent ferrocene is added to group C, and the amount of ferrocene added is 15% of the total weight of the slurry solid content. The pore-forming agent ferrocene is added to group D, and the amount of ferrocene added is 20% of the total weight of the slurry solid content. The solid content of the positive electrode groups A, B, C and D is 67%, and the negative electrode formula is 95% graphite+2% SBR+2% CMC+1% SP, solid content is 55%, the above positive and negative electrode slurries are prepared into pole pieces by coating and rolling processes, wherein the baking temperature for removing solvent in the positive electrode coating process is 70°C, and the baking temperature for removing solvent in the negative electrode coating process is 60°C. The coating surface density of group A positive electrode after removing solvent is 19.3 mg / cm 2 After removing the solvent, the coating surface density of group B positive electrode is 20.26 mg / cm 2 After removing the solvent, the coating surface density of the positive electrode of group C is 22.19 mg / cm 2 After removing the solvent, the coating surface density of the positive electrode of group D is 23.16 mg / cm 2 The negative electrode surface density is 9.3 mg / cm 2The thickness of the positive electrode after rolling is 120μm±2μm, and the rolling pressure is 50 tons. The thickness of the negative electrode after rolling is 160μm±2μm, and the rolling pressure is 55 tons. The positive electrode group A does not contain a pore-forming agent and does not require a heating pore-forming process. The positive electrode groups B, C and D contain pore-forming agent ferrocene. The pole pieces of groups B, C and D are heated to remove the pore-forming agent. The heating temperature is 150°C and the heating is performed for 1 hour. After the pore-forming agent ferrocene in the heated pole piece is sublimated, a pore structure will be left in the pole piece. The pore can provide a channel for lithium ion transmission, thereby increasing the battery's rate performance, that is, the battery's power characteristics. The diaphragm is made of PE material, the electrolyte is a mixed solvent of 1mol / L lithium hexafluorophosphate + EC + DEC + DMC (the solvent volume ratio is 3:4:3), and the whole battery is assembled for testing. The size of the positive electrode piece is 74mm*106mm, and the size of the negative electrode piece is 76mm*108mm. The assembled battery adopts the stacking process, and the number of stacks is 5 for the positive electrode and 6 for the negative electrode. The stacked battery is baked at 85℃ for 24 hours to remove the moisture in the battery. After the baked battery is injected with liquid and then formed, a battery with a capacity of about 2Ah is prepared. The battery is assembled using different groups of pole pieces. The battery numbers and rate performance test results of different combinations are as follows:

[0019]

[0020] In the embodiment, the 10C discharge capacity retention rate of group a (10C discharge capacity value / 1C discharge capacity value*100%) is 80.1%-80.5%, the 10C discharge capacity retention rate of group b is 91.1%-91.7%, the 10C discharge capacity retention rate of group c is 95.2%-95.3%, and the 10C discharge capacity retention rate of group d is 94.5%-94.4%. Compared with groups a, b, c, and d, the performance of groups b, c, and d is improved compared with that of group a. This is because the addition of the pore-forming agent increases the porosity of the electrode sheet after rolling, reduces the ion transfer resistance in the electrode sheet, increases the lithium ion transmission efficiency, and effectively improves the rate performance of the battery. Compared with groups b, c, and d, group c has the best performance. Group d has a decreased performance due to the addition of too high a content of the pore-forming agent. This is mainly because the high porosity leads to an excessively large distance between the electrode sheet material particles, a decrease in electronic conductivity, and a decrease in the final battery rate performance. Therefore, the content of the pore-forming agent needs to be controlled within a reasonable range.

[0021] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing an electrode sheet, comprising a current collector and an electrode coating attached to the current collector, characterized in that: The electrode is a positive electrode sheet or a negative electrode sheet; the electrode coating is coated on the current collector by slurry coating, and the specific process is as follows: 1) preparing slurry: adding a pore-forming agent to the slurry containing the electrode coating material, wherein the amount of the pore-forming agent added is 0.5%-15% of the mass of the electrode coating material, preferably 5-15%, and more preferably 5-10%; 2) coating the slurry on the current collector and forming the electrode through drying and rolling process, wherein the drying temperature is lower than the sublimation temperature of the pore-forming agent minus 30°C or less; 3) The electrode sheet after rolling is baked to sublime the pore-forming agent and remove the pore-forming agent in the coating slurry. The baking temperature is greater than the sublimation temperature of the pore-forming agent plus 20°C or more.

2. The preparation method according to claim 1, characterized in that: The slurry includes a positive electrode or negative electrode active material, a solvent, a binder, a conductive agent, and a pore-forming agent added to the slurry in an amount of 0.5% to 15% of the total weight of the solid materials except the solvent, preferably in the range of 5% to 15%, and more preferably in the range of 5% to 10%; The positive electrode active material is one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, lithium iron manganese phosphate and other lithium battery positive electrode materials; The negative electrode active material is one or more of graphite, soft carbon, hard carbon, mesophase microspheres, silicon carbon and other negative electrode materials; The solvent negative electrode is deionized water, and the positive electrode is N-methylpyrrolidone; The binder used in the positive electrode plate is polyvinylidene fluoride (PVDF); the binder used in the negative electrode plate is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR); The conductive agent is one or two of conductive carbon black (SP) or carbon nanotubes and graphene.

3. The preparation method according to claim 1 or 2, characterized in that: The pore-forming agent is one or more organic or inorganic substances that sublime under heating conditions; preferably one or more ferrocene, camphor, iodine, benzoic acid, and more preferably ferrocene.

4. The preparation method according to claim 3, characterized in that: The particle size of the pore-forming agent is 2 μm<D50<30 μm, preferably 2 μm<D50<15 μm, and more preferably 2 μm<D50<10 μm.

5. The preparation method according to claim 1 or 2, characterized in that: The slurry is coated on the current collector and dried to obtain a positive electrode or negative electrode coating, wherein the drying temperature is below the sublimation temperature of the low-temperature pore-forming agent minus 30° C.; The coating surface density of the positive electrode after removing the pore-forming agent is 5-30 mg / cm 2 After removing the pore-forming agent from the negative electrode, the coating surface density is 2-20 mg / cm 2 .

6. The preparation method according to claim 1 or 2, characterized in that: After rolling, the temperature of the electrode sheet for baking the sublimated pore-forming agent is higher than the sublimation temperature of the pore-forming agent plus 20°C or more.

7. The preparation method according to claim 6, characterized in that: The time for baking the sublimation pore-forming agent is at least 5 minutes or more, preferably in the range of 20 minutes to 80 minutes, and more preferably in the range of 40 minutes to 60 minutes.

8. The preparation method according to claim 1 or 2, characterized in that: The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

Citation Information

Patent Citations

  • Thick electrode with good electrochemical performance and its preparation method

    CN102324493A

  • Pore-forming method for diaphragms of lithium ion batteries

    CN102655229A

  • Hollow sulfur electrode material coated with conductive polymer for lithium sulfur battery through utilizing sublimation material

    CN110311102A

  • Pole piece, preparation method thereof and lithium ion battery

    CN110752345A

  • Electrode plate and preparation method and application thereof

    CN112151764A